Comparative Analysis of Organic Manures to Chemical Fertilizers on the Growth and Yield of Okra at Sunsari, Nepal - Budha Magar, Supriya; Timilsina, Dinesh; Timilsina, Umesh (Journal of Agriculture and Forestry University, 2026)
Okra (Abelmoschus esculentus), a warm-season crop of the Malvaceae family, is widely cultivated in the tropical and subtropical regions of Nepal. Organic manure plays an important role in improving its growth and yield; however, optimal application rates remain insufficiently studied in the Terai region of Eastern Nepal. A field experiment was conducted from February to April 2025 in Inaruwa-3, Sakhuwagachhi, Sunsari to evaluate the effects of different organic manures on the growth and yield of okra variety NS-864. The experiment was arranged in a Randomized Complete Block Design (RCBD) with seven treatments: poultry manure, vermicompost, farmyard manure (FYM), goat manure, mustard oil cake, , and a control, each replicated three times. Data were collected from five randomly selected plants per plot. Early seed germination (90%) was recorded at 11 days after sowing in goat manure and FYM treatments. Among organic sources, poultry manure significantly enhanced growth and yield attributes, producing the highest number of primary branches and average pod weight, second only to NPK. FYM showed moderate performance, while vermicompost and mustard oil cake were less effective. The control produced the lowest yield. Overall, poultry manure proved to be the most effective organic alternative for sustainable okra production under Eastern Nepal conditions.